Impact of yellow fever outbreaks on two howler monkey species (Alouatta guariba clamitans and A. caraya) in Misiones, Argentina - Holzmann, Ingrid (2010)
Two yellow fever outbreaks (YFOs) ocurred in northeastern Argentina between November 2007 and October 2008, seriously affecting populations of two howler monkey species: the brown howler Alouatta guariba clamitans and the black howler Alouatta caraya. Both howlers live syntopically in El Piñalito Provincial Park, Misiones, where four groups (36 individuals) were studied since January 2005. The first dead howlers were found on January 20, 2008, in El Piñalito. Systematic searches found 14 dead howlers within the area (12 from the study groups and two from neighboring groups), with only two young seen on January 25, 2008, and none found since up to December 2008. In October 2008, another YFO hit howler monkey populations from El Soberbio, Misiones. Overall, 59 howlers were found dead in Misiones from November 2007 to December 2008. Thanks to the alert of the howler's death in El Piñalito, a prompt human vaccination campaign started in the area. Wild howler monkey populations from both species are in a delicate situation in Misiones, especially the brown howler, an already endangered species in Argentina and endemic to the Atlantic Forest. If we add the recurrence of YFOs to the reduction of suitable habitat to small fragments, it could be only a matter of time until howler populations disappear from the Upper Paraná Atlantic Forest in Misiones.